The Effect Of Service Quality and Promotion On Customer Loyalty With Customer Satisfaction as an Intervening Variable at PT. Jetindo Nagasakti Transekspress Medan - Christopher Alexander Mahidin; Nagian Toni; Fenny Krisna Marpaung; Alex Tribuana Sutanto; Hendry Hendry (Jurnal of Management and Social Sciences, 2024)
The purpose of this research was to determine the influence of service quality and promotion on customer loyalty with customer satisfaction as an intervening variable at PT. Jetindo Nagasakti Transekspress Medan. The method used in this research is a quantitative descriptive method which is carried out through data collection using questionnaires and statistical testing data analysis. The samples taken in this research were all customers who had used the services of PT. Jetindo Nagasakti Transekspress Medan, numbering 85 people. The data analysis used is path analysis using the IBM SPSS Statistics version 26 application. The research results show that Service Quality influences customer satisfaction at PT. Jetindo Nagasakti Transekspress Medan. Promotions influence customer satisfaction at PT. Jetindo Nagasakti Transekspress Medan. Service quality influences customer loyalty at PT. Jetindo Nagasakti Transekspress Medan. Promotions influence customer loyalty at PT. Jetindo Nagasakti Transekspress Medan. Customer satisfaction influences customer loyalty at PT. Jetindo Nagasakti Transekspress Medan. Service quality influences customer loyalty with customer satisfaction as an intervening variable at PT. Jetindo Nagasakti Transekspress Medan. Promotions influence customer loyalty with customer satisfaction as an intervening variable at PT. Jetindo Nagasakti Transekspress Medan.